The history of Lyme disease in Italy and its spread in the Italian territory - Trevisan, Giusto; Ruscio, Maurizio; Cinco, Marina; Nan, Katiuscia; Forgione, Patrizia; Di Meo, Nicola; Tranchini, Paolo; Nacca, Massimo; Trincone, Silvana; Rimoldi, Sara Giordana; Giacomet, Vania; Ricci, Michela; et al. (Frontiers in pharmacology, 2023)
Lyme borreliosis (LB) is the most common vector-borne zoonotic inflammatory disease in the Northern Hemisphere. In Italy, the first case was diagnosed in 1985 in a woman in Liguria, while the second, in 1986 in Friuli-Venezia Giulia, documenting the infection in northern Italy. Both diagnoses were confirmed by serological assessment by an indirect immunofluorescence (IFI) technique. Borrelia cultivation from both Ixodes ricinus ticks and human lesions in Trieste (Friuli-Venezia Giulia) identified Borrelia afzelii as the prevalent genospecies; nevertheless, Borrelia garinii , Borrelia burgdorferi ( sensu stricto ), and Borrelia valaisiana (VS116 Group) were also detected, although less frequently. LB was also documented in other Italian regions: in Tuscany (1991), Trentino–Alto Adige (1995–1996), Emilia-Romagna (1998), Abruzzo (1998), and more recently, Lombardy. Nevertheless, data on LB in other Italian regions, especially in southern Italy and islands, are poor. The aim of this study is to document the spread of LB in Italy through the collection of data from LB patients in eight Italian hospitals located in different Italian regions. Diagnostic criteria for LB diagnosis are as follows: i) the presence of erythema migrans (EM) or ii) a clinical picture suggestive of LB, confirmed by serological tests and/or PCR positivity for Borrelia detection. In addition, data also included the place of residence (town and region) and the place where patients became infected. During the observation period, 1,260 cases were gathered from the participating centers. Although different in extent from northern Italy to central/southern Italy, this study shows that LB is widespread throughout Italy.